1993
DOI: 10.1128/jvi.67.2.1058-1066.1993
|View full text |Cite
|
Sign up to set email alerts
|

NF-IL6 represses early gene expression of human papillomavirus type 16 through binding to the noncoding region

Abstract: The expression of human papillomavirus type 16 (HPV16) early genes, including E6 and E7 transforming genes, is regulated by several cellular factors binding to the noncoding region (NCR), such as the glucocorticoid receptor, NF-I, and AP1, all of which are positive regulators. We demonstrated that the nuclear factor for interleukin 6 expression (NF-EL6) specifically binds to the HPV16 NCR ranging from nucleotides 7007 to 7766 and represses the early gene expression of HPV16. The responsive element in HPV16 NCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2
3

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 51 publications
4
25
2
3
Order By: Relevance
“…Our results are different from those presented in two reports studying the HPV 11 LCR in which C/ EBPb seems to act as a repressor in primary human keratinocytes [40,41]. In contrast to our results, Kyo and coworkers [31] observed that C/EBPb repressed the HPV16 LCR in several cell lines in transient transfection experiments. In this latter study as well as in several other studies reporting a repression instead of an activation of the transcriptional activity by C/EBPb, the CMV±C/EBPb I expression vector was used [17,31,42].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results are different from those presented in two reports studying the HPV 11 LCR in which C/ EBPb seems to act as a repressor in primary human keratinocytes [40,41]. In contrast to our results, Kyo and coworkers [31] observed that C/EBPb repressed the HPV16 LCR in several cell lines in transient transfection experiments. In this latter study as well as in several other studies reporting a repression instead of an activation of the transcriptional activity by C/EBPb, the CMV±C/EBPb I expression vector was used [17,31,42].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, Kyo and coworkers [31] observed that C/EBPb repressed the HPV16 LCR in several cell lines in transient transfection experiments. In this latter study as well as in several other studies reporting a repression instead of an activation of the transcriptional activity by C/EBPb, the CMV±C/EBPb I expression vector was used [17,31,42]. CMV±C/EBPb I contains the full-length C/EBPb-gene that can produce LAP and LIP by a leaky ribosome scanning mechanism [10] ( Figure 6, lane 3 in both panels).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…19 The cytokines exerting inhibitory effects on HPV gene expression and decreasing cell proliferation are tumor necrosis factor-alpha (TNFα), interleukin-1 (IL-1), transforming growth factor-beta (TGFβ), interferons (IFNs), and others (leukoregulin, epidermal growth factor (EGF) ( Table 2). [20][21][22][23][24][25][26][27][28][29] The mechanism of downregulation of the expression of HPV E6 and E7 oncogenes seems to involve the activation of certain transcriptional factors, 24 whereas the inhibition of cell proliferation may be primarily related to the decrease in the expression of both viral and cellular oncogenes. 20 Some cytokines (e.g.…”
Section: Cytokines Inhibiting Hpv Genome Expression and The Proliferamentioning
confidence: 99%